2016
DOI: 10.1097/shk.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Conditioning Influences Mitochondrial Dynamics

Abstract: Remote ischemic preconditioning (RIPC) has emerged as an attractive strategy to protect the heart against ischemia-reperfusion (I/R) injury. The mechanisms by which remote ischemic conditioning (RIC) is protective are to date unknown, yet a well-accepted theory holds that the mitochondria play a central role. Mitochondria are dynamic organelles that undergo fusion and fission. Interventions that decrease mitochondrial fission or increase mitochondrial fusion have been associated with reduced I/R injury. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Moreover, preservation of mitochondrial morphology via IPC has been previously shown to confer cardioprotection in the setting of IRI 11,3840 . Although IPC has been suggested to preserve the function of SSM mitochondria following IR, we did not observe any IPC-induced preservation of SSM mitochondria morphology following ischemia-only treatment 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, preservation of mitochondrial morphology via IPC has been previously shown to confer cardioprotection in the setting of IRI 11,3840 . Although IPC has been suggested to preserve the function of SSM mitochondria following IR, we did not observe any IPC-induced preservation of SSM mitochondria morphology following ischemia-only treatment 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…It is confirmed that I/R down‐regulates the expression of mitochondrial fusion proteins including Mfn1, Mfn2, and Opa1, disrupts mitochondrial fusion and increases cardiomyocyte apoptosis (Cellier et al, ; Dong, Chen, et al, ; Yang et al, ; Yu et al, , ; Zhao et al, ). Multiple lines of evidence suggest that inhibition of endogenous fusion proteins enhances I/R‐induced cardiomyocyte apoptosis, and up‐regulation of fusion proteins suppresses I/R‐induced cardiomyocyte apoptosis.…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 87%
“…The studies also identified Mfn2 as a novel target of SIRT1 in which SIRT1 deacetylates Mfn2 to mediate autophagy induction [212, 213]. Male adult rats exposed to four 5-min cycles of limb ischemia interspersed by 5 min of limb reperfusion, immediately prior to myocardial ischemia and 120 min of reperfusion (MI + RIPC group) experienced a smaller infarct size (−28%), increased mitochondrial fusion protein OPA1, and preserved mitochondrial morphology [214]. A mild overexpression of OPA1 also protected against cardiac ischemic injury measured in the form of reduced LDH release in 5 months old mice subjected to a Langendorff model of 40 min of ischemia followed by 15 min of reperfusion [215].…”
Section: Mitochondrial Fusion and Fission Proteins In Cardiac Health mentioning
confidence: 99%
“…Remote ischemic preconditioning (RIPC) has been shown to induce upregulation of OPA1 [214], and sevoflurane postconditioning has been reported to suppress the decline of OPA1 and increase in f Drp1 and Parkin induced by IRI [234]. …”
Section: Therapeutic Targeting Of Mitochondrial Fusion and Fission Prmentioning
confidence: 99%